Kompres Hangat dengan Jahe Sebagai Metode Pengurangan Intensitas Nyeri Pada Lansia dengan Arthritis Rheumatoid - Nuriza Agustina; Raden Surahmat; Mareta Akhriansyah; Dian Emiliasari; Muhamad Andika Sasmita Saputra (Jurnal Akademika Baiturrahim Jambi, 2023)
Pain management in Rheumatoid Arthritis aims to reduce or eliminate pain and discomfort. Warm compresses with ginger become one of complementary treatment which can reduce pain in rheumatoid arthritis sufferers because ginger contains the enzyme cyclo-oxygenase. The aims determine the effect of warm compresses with ginger on pain intensity in the elderly with rheumatoid arthritis. The methode This research is a quantitative design with a Pre Experiment approach (One group pretest and posttest design). Conducted at 23 Ilir Health Center Palembang. The sample in this study were elderly people with rheumatoid arthritis at the 23 Ilir Health Center Palembang in 2022, totaling 30 people. The results indicate that the average pain score before warm compresses with ginger is 5.57, the lowest pain score before warm compresses with ginger is 3 and the highest score is 9. The average pain score after warm compresses with ginger is 3.80, the score is 3.80. pain after a warm compress with ginger the lowest was 2 and the highest score was 6. There was an effect of warm compress with ginger on pain intensity in the elderly with rheumatoid arthritis (ρ=0.000), with an average difference of 1.77 scores. Based on the results of the study for Public Health 23 Ilir Palembang, it is hoped that it can be used as a reference for determining policies in overcoming and improving health, especially the elderly who have the pain.